Viskositas dan Aktivitas Antibakteri Sabun Cair Berbasis VCO dengan Penambahan Ekstrak Etanol Daun Kelor (Moringa oleifera) Terhadap Bakteri Patogen: Viscosity and Antibacterial Activity of VCO-Based Liquid Soap with Addition of Ethanol Extract of Moringa Leaf (Moringa oleifera) Against Pathogenic Bacteria - Pasjan Satrimafitrah; Mohamad Afdal; Jusman; Abd. Rahman Razak; Ahmad Ridhay; Nov Irmawati Inda (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2022)
This research was conducted by making VCO-based liquid soap with the addition of ethanol extract from Moringa leaves (Moringa oleifera). The purpose of this research was to determine the mass ratio of ethanol extracts of Moringa leaves and Virgin Coconut Oil (VCO) which produces soap with the highest antibacterial activity against tested bacteria. The other purpose is to determine the effect of the mass ratio against the viscosity of liquid soap. The research design used was a Completely Randomized Design (CRD) with the independent variables being the mass ratio of Moringa leaf ethanol extract and VCO which consists of five levels of 0:75 (F1), 1.5:73.5 (F2), 3:72(F3), and 4.5:70.5(F4) (w/w). The soap produced was tested for antibacterial activity againts Staphylococcus aureus, Escherichia coli, and Staphylococcus epidermidis using agar diffusion method as well as viscosity tests. The results showed that the antibacterial activity of liquid soap tends to be higher with increasing levels of ethanol extract of Moringa leaves. The liquid soap formula with the ratio of Moringa leaf ethanol extract: VCO of 3:72 (w/w) (Formula F3) had relatively higher antibacterial activity against the three tested bacteria. The inhibition zones against Staphylococcus aureus, Escherichia coli, and Staphylococcus epidermidis were 22.302 mm, 33.230 mm, and 36.490 mm, respectively, while the viscosity value of liquid soap was 47.433 cP.